Nanostructured high-performance electrolyte membranes based on polymer network post-assembly for high-temperature supercapacitors - Zeng, Minghao; Guo, Haikun; Wang, Gang; Shang, Lichao; Zhao, Chengji; Li, Haolong (Journal of colloid and interface science, 2021)
[Display omitted] •A post-assembly strategy was developed to prepare nanostructured PEMs.•Bicontinuous PEMs with high stability and high proton conductivity were prepared.•The PEM-based HT-SCs exhibited a high capacitance of 138.0 F g−1 at 150 ℃.•The HT-SCs showed a high capacitance retention of 80% after 2500 cycles at 150 ℃. The development of high-temperature supercapacitors highly relies on the explore of stable polymer electrolyte membranes (PEMs) with high ionic conductivities at high-temperature conditions. However, it is a challenge to achieve both high stability and high conductivity in a PEM at elevated temperatures. Herein, we report the fabrication of high-performance proton conductive PEMs suitable for high-temperature supercapacitors (HT-SCs), which is based on a post-assembly strategy to control the rearrangement of polymer networks in the PEMs. This strategy can create cross-linked PEMs with bicontinuous nanostructures, as well as highly stable and highly conductive features. Specifically, a series of bicontinuous PEMs are prepared by the controllable cross-linking of poly(ether-ether-ketone) and poly(4-vinylpyridine), followed by the inducement of phosphoric acid. These PEMs exhibit both a high proton conductivity of 70 mS cm−1 and a high modulus of 39.3 MPa at 150 ℃, which can serve as high-performance electrolytes. The HT-SCs based on these PEMs display a specific capacitance of 138.0 F g−1 and a high capacitance retention of 80.0% after 2500 galvanostatic charge–discharge cycles at 150 ℃, exhibiting excellent high-temperature capacitance and cycle stability. This post-assembly concept can provide a new route to design high-performance PEMs for HT-SC and other energy device applications.